ANALISIS DAN PENGARUH KONDISI INTERNAL USAHATANI KOPI ARABIKA TERHADAP PARTISIPASI PETANI DALAM KELOMPOK TANI DI KABUPATEN SAMOSIR, SUMATERA UTARA - Hotden Leonardo Nainggolan; Albina Ginting; Yanto Raya Tampubolon (Universitas Garut, 2026)
The sustainability and performance of Arabica coffee farming systems are not solely influenced by external interventions but are strongly shaped by farmers’ internal conditions that determine institutional engagement and collective action. This study aims to examine the internal environment of Arabica coffee farming and assess its influence on farmers’ participation in farmer groups in Ronggur Nihuta District, Samosir Regency, North Sumatra Province. The study was purposively conducted in Ronggur Nihuta and Paraduan villages, involving 30 Arabica coffee farmers as respondents. Primary data were collected through structured interviews and field observations, while secondary data were obtained from official government sources. The internal farming environment was analyzed descriptively using a Likert scale to construct an Internal Environmental Condition Index (IECI), whereas its effect on farmers’ participation was examined using multiple linear regression analysis. The results indicate that the internal environment of Arabica coffee farming is categorized as very strong, as reflected by IECI values exceeding 90 across all indicators, including farmers’ interest, creativity, natural resource and land potential, and infrastructure availability. Partially, all internal variables exert a positive and statistically significant influence on farmers’ participation in farmer groups, with natural resource and land potential emerging as the most influential factor. Simultaneously, the internal environment variables account for 53% of the variation in farmers’ participation levels. These findings underscore the importance of integrating psychological factors, farmers’ adaptive capacities, and physical resource support in strengthening farmer institutions. This study contributes to the agricultural socio-economic literature by positioning internal environmental factors as a critical foundation for policy formulation aimed at promoting sustainable and competitive Arabica coffee farming systems.